COMPARATIVE CLAUSES IN BRAZILIAN SIGN LANGUAGE: AN ANALYSIS OF INTERVIEWS WITH DEAF REFERENCE FROM THE LIBRAS CORPUS - Ludwig, Carlos Roberto (Acta Semiótica et Lingvistica, 2026)
This paper describes the linguistic properties of comparative adverbial clauses in Brazilian Sign Language (Libras), which establish relationships of equality, superiority, or inferiority between signed events. Analyzing data from four Deaf Reference Participants in the Libras Corpus (two women and two men). The study utilized ELAN software with specialized annotation tiers to categorize complex sentence units. The findings reveal that comparative hypotaxis is articulated comprising lexical connectives, such as IGUAL, MAIS, MAIS... DO-QUE, POUCO, and MAIS-OU-MENOS, and asyndetic juxtaposition, where the comparative proposition emerges directly from the discursive context. Furthermore, the research highlights the critical role of non-manual markers, including eye-blinks, squinted eyes, raised eyebrows, and trunk/head rotation, alongside the strategic use of referential space to map compared events to the right and left loci. Ultimately, these results demonstrate that comparative hypotaxis in Libras relies on the sophisticated integration of manual signs, use of space, and prosodic non-manual markers to combine complex linguistic propositions.